Induction of in vivo Pig-a gene mutation but not micronuclei by 5-(2-chloroethyl)-2ʹ-deoxyuridine, an antiviral pyrimidine nucleoside analogue. (15th September 2018) - Elhajouji, Azeddine; Vaskova, Dagmara; Downing, Rebecca; Dertinger, Stephen D; Martus, Hansjeorg
Abstract: 5-(2-Chloroethyl)-2ʹ-deoxyuridine (CEDU) was developed as an antiviral drug. It has been studied in a number of in vitro and in vivo genotoxicity assays and is considered an unusual nucleoside analogue owing to its potent mutagenic potential, with little to no measurable clastogenic activity. Given this atypical profile, CEDU represented an interesting compound for evaluating the in vivo Pig-a gene mutation assay, a test that is undergoing extensive validation for regulatory safety applications. The current report describes two studies with 7-week-old male Wistar Han rats, one that exposed animals to several dose levels of CEDU for 5 consecutive days, the other for 28 consecutive days. Blood samples were collected at several time points and analysed for Pig-a mutant cell frequencies via flow cytometry. These Pig-a analyses were accompanied by micronucleated reticulocyte (MN-RET) measurements performed with blood samples collected 1 day after cessation of treatment. Both studies showed robust CEDU dose-related increases in Pig-a mutant reticulocytes and mutant erythrocytes. Conversely, neither experiment showed evidence of a CEDU-related MN-RET-inducing effect. These rat haematopoietic cell results were in good agreement with those of earlier mouse studies where in vivo mutagenesis was observed, without clastogenicity/aneuploidy. Taken together, these data add further support to the concept that the Pig-a assay represents an important complement to the widely used in vivo micronucleus assay, as it expands the range of important DNA lesions that can be detected in short-term as well as protracted exposure study designs.